The effects on ruminal pH and serum haptoglobin after feeding a grain-based supplement to grazing dairy cows as a partial mixed ration or during milking. Issue 1 (April 2015) - Coombe, J.E.; Pyman, M.F.; Mansell, P.D.; Auldist, M.J.; Anderson, G.A.; Wales, W.J.; Conley, M.J.; Manos, S.; Hannah, M.; Fisher, A.D.
Highlights Grazing cows fed supplement during milking or as a partial mixed ration on a feedpad. Ruminal pH and serum haptoglobin (Hp) concentrations were measured. Supplement feeding method did not affect ruminal pH or serum Hp.